2016
DOI: 10.5603/kp.a2015.0174
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making microRNAs (miR-124, -133a/b, -34a and -134) in patients with occluded target vessel in acute coronary syndrome

Abstract: A b s t r a c tBackground: Coronary artery occlusion does not always manifest with ST-elevation, and some patients can have patent coronary vessel. Aim:We evaluated circulating microRNA (miRNA) profiles to discriminate subjects with infarct-related artery (IRA) occlusion. Methods and results:Patients (n = 43) with uncomplicated acute coronary syndrome and positive troponins were classified with respect to patent vs. occluded IRA or ST-elevation vs. non-ST elevation MI (STEMI vs. NSTEMI). Expression levels of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
48
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 22 publications
1
48
2
3
Order By: Relevance
“…Previously described as potential AMI diagnostic markers, miR-133a, miR-208b, 22,35 as well as miR-499 and miR-451, 22 and miR-134 24 levels were reported as higher in STEMI, when compared with non-STEMI. In contrast, two studies of miR-499 24,35 showed no significant difference in miR expression. A combination of miR-486 and miR-150 39 was reported to be sensitive and specific for the discrimination of non-STEMI cases from non-AMI controls, but not for discriminating non-STEMI from STEMI.…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…Previously described as potential AMI diagnostic markers, miR-133a, miR-208b, 22,35 as well as miR-499 and miR-451, 22 and miR-134 24 levels were reported as higher in STEMI, when compared with non-STEMI. In contrast, two studies of miR-499 24,35 showed no significant difference in miR expression. A combination of miR-486 and miR-150 39 was reported to be sensitive and specific for the discrimination of non-STEMI cases from non-AMI controls, but not for discriminating non-STEMI from STEMI.…”
Section: Resultsmentioning
confidence: 84%
“…miR-133a, 24,33 miR-134, miR-145, 25 miR-122, and miR-370 26 were associated with CAD presence, even after adjustment for other cardiovascular risk factors. Furthermore, their levels were positively correlated with the severity of CAD quantified by the Gensini score, in other words, may be used to predict both the presence and severity of coronary lesions in CAD patients.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations